(untitled) (Razi Medical Journal, 2025)
We are delighted to announce the launch of Razi Medical Journal (RMJ), a new peer-reviewed, open-access medical journal committed to fostering innovation, collaboration, and excellence in medical research and practice. As the editorial team, we enthusiastically invite you to contribute your groundbreaking work to our inaugural issue. The field of medicine is advancing at an unprecedented pace, driven by groundbreaking discoveries, emerging technologies, and evolving healthcare challenges. RMJ strives to be a premier platform for publishing high-quality research, clinical insights, and transformative ideas that will shape the future of healthcare. Our mission is to bridge the gap between research and practice, fostering collaboration among diverse perspectives to address the most pressing issues in modern medicine.